The boneless flower and bird painting art: a comparison study between traditional and modern approach on Lin Ruoxi’s artworks / Feifei Duan, Issarezal Ismail and Ishak Ramli - Duan, Feifei; Ismail, Issarezal; Ramli, Ishak (Universiti Teknologi MARA, Perak, 2024)
Lin Ruoxi is one of the representative painters of the contemporary Lingnan School of Painting, and one of the main representative painters of contemporary boneless paintings. His boneless paintings have a distinctive personal style and have a profound influence on the creation of contemporary boneless paintings. The main purpose of this paper is to explore the modernity of Lin Ruoxi's boneless paintings from the perspective of stylistics and select Lin Ruoxi's representative works of boneless paintings in the past 40 years as the research objects. The photos are compared with conventional boneless paintings from five perspectives—technique, composition, colour, form, and medium and the differences are summarised. Specifically, the observation and comparison approach is employed for the research. The study discovered that Lin Ruoxi's boneless painting technique had incorporated numerous other painting techniques based on tradition; the composition makes use of the plane composition principle; the colour draws inspiration from the colouring style of contemporary Japanese painting; the shape is refined and generalised to be more refined, with imagery; and the choice of media tends to be creative and diverse. The analysis of Lin Ruoxi's boneless painting style reveals that while it has its roots in traditional Chinese painting, it is inclusive, pioneering, and innovative, bringing his creations more in line with the demands of contemporary aesthetics. The great eclecticism and modernism in the artistic philosophy are evident.